The Accepatance Of Green Supply Chain Management On Micro-Businesses In UUM - Mohd Yusoff, Yuhainis; Alias, Syafiqah; Mohd Zamani, Siti Norhasmaedayu (Emerging Advances in Integrated Technology, 2023)
Many companies have increased their resources and capabilities in response to the growing need for green supply chain management (GSCM) brought on by globalisation. These necessities are now essential for domestic and international competition. With increasing consumer awareness of environmental issues, micro businesses need to implement strategies to reduce the environmental impact of their products and services. This paper analyzed acceptance of GSCM among micro businesses at Universiti Utara Malaysia (UUM). As a university no.2 in Malaysia, GSCM among micro businesses is necessary. Moreover, this paper aims to be a comprehensive survey on technological organizational and environmental factors influence the acceptance of green supply chain practices on micro businesses in UUM. The sampling of the study focuses on micro-businesses in UUM and this study will be carried out through interviews which is qualitative. From the data analysis that we collect, we can see that the acceptance of GSCM in micro-businesses can influenced by many factors but the adoption will give great impact on micro businesses. As overall, we can see GSCM acceptance are influenced in terms of technology, organisation, and environment factor, which are able to influence the decisions that micro businesses make to further practise GSCM in their day-to-day operations. Finally, limitations and directions for future studies are provided in the conclusion section.